2013
DOI: 10.1371/journal.pone.0077308
|View full text |Cite
|
Sign up to set email alerts
|

Chafuroside B, an Oolong Tea Polyphenol, Ameliorates UVB-Induced DNA Damage and Generation of Photo-immunosuppression Related Mediators in Human Keratinocytes

Abstract: Chafuroside B was recently isolated as a new polyphenolic constituent of oolong tea leaves. However, the effects of chafuroside B on skin function have not been examined. In this study, we investigated the protective effects of chafuroside B against UVB-induced DNA damage, apoptosis and generation of photo-immunosuppression related mediators in cultured normal human epidermal keratinocytes (NHEK). Chafuroside B at 1 µM attenuated both UVB-induced apoptosis, evaluated in terms of caspase-3/7 activity, and UVB-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Kumar et al [79] found that a combination of ellagic acid with curcumin (25 μM each) caused SBs while the separate compounds had no significant effect. A decrease in (background) SBs with epigallocatechin gallate or epicatechin gallate was reported by Durgo et al [36] at 48 but not 72 h. At more reasonable concentrations, the results are mixed: decreases in UV(B)-induced SBs [70] and cyclobutane pyrimidine dimers [72]; decreases in H 2 O 2 -induced SBs and MN [74]; a decrease in SBs induced by cumene hydroperoxide [75]; but SBs and Fpg-sites increased in tetradecanoyl phorbol acetate (TPA)-stimulated neutrophils [78] and an increase in SBs with ellagic acid in prostate cancer cells was reported by Vanella et al [73] at concentrations of 9 μM in one of the cell lines but higher concentrations in two other lines.…”
Section: Isolated Phytochemicalsmentioning
confidence: 89%
“…Kumar et al [79] found that a combination of ellagic acid with curcumin (25 μM each) caused SBs while the separate compounds had no significant effect. A decrease in (background) SBs with epigallocatechin gallate or epicatechin gallate was reported by Durgo et al [36] at 48 but not 72 h. At more reasonable concentrations, the results are mixed: decreases in UV(B)-induced SBs [70] and cyclobutane pyrimidine dimers [72]; decreases in H 2 O 2 -induced SBs and MN [74]; a decrease in SBs induced by cumene hydroperoxide [75]; but SBs and Fpg-sites increased in tetradecanoyl phorbol acetate (TPA)-stimulated neutrophils [78] and an increase in SBs with ellagic acid in prostate cancer cells was reported by Vanella et al [73] at concentrations of 9 μM in one of the cell lines but higher concentrations in two other lines.…”
Section: Isolated Phytochemicalsmentioning
confidence: 89%
“…Exposure to UVB radiation is a primary cause of skin photoageing, characterized by skin wrinkles, roughness, laxity, irregular pigmentation, telangiectasia, atrophy and neoplasia . The major aspects of the pathogenesis of skin photoageing induced by UVB include skin wrinkle formation, epidermal thickening , degradation of matrix macromolecules by MMPs , ROS‐mediated inflammation and keratinocyte apoptosis . Because these processes in UVB‐induced skin photoageing could be inhibited by antioxidants of natural origin , efforts have been made to identify antioxidants that could protect against or prevent photoageing due to UVB exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to UV light, leading to mass apoptosis, could compromise the natural barrier function of the skin and accelerate photoageing. This suggests that the inhibition of epidermal keratinocyte apoptosis may represent a therapeutic method for blocking of photoageing .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also envisaged that CFA and CFB could play an active role in the development of new cosmetics because they have been reported to show excellent anti-wrinkle activity. 25,26) Although there are numerous potential applications for CFA and CFB, these compounds have only ever been isolated in small quantities from oolong tea leaves. 22,23) With this in mind, it was envisaged that orally disintegrating tea tablets (ODTTs) containing much larger amounts of these active ingredients could be prepared by the microwave irradiation of wet molded tablets, without the need for any additional operations such as extraction.…”
mentioning
confidence: 99%